Stock Price and Performance of Indonesian Banking, Case Study for The Period of 2013-2016 - Wibowo, Cornelius Candra Adi; Sukoco, Agus; Wulandari, Ani; Bhukuth, Augendra (AIBPM Publisher, 2018)
The purpose of this study is to analyze the effect of Return On Assets, Return On Equity and Earning Per Share to stock prices of Banking Companies listed in Indonesia Stock Exchange (IDX) during 2013-2016. This study analyzes the profitability ratios of financial statements of banking companies and their impact on stock prices. Method, The population of this research is Banking Companies listed in IDX during 2013-2016. Samples used are as many as 10 Banking companies with purposive sampling technique to determine the sample based on certain criteria. The analytical technique used is Multiple Regression Analysis. The data is financial statements downloaded from Indonesia Stock Exchange website and tested with SPSS 18 application. Result, Result of this study is that the performance of Indonesian banking is influenced by Return On Asset (ROA), Return On Equity (ROE), which have a significant influence on Stock Price, however Earning Per Share (EPS) has no significant effect on Stock Price. The findings of this study are banking companies that go public in Indonesia, their Stock Price is determined by the value of ROA and ROE and this will assist to provide useful information to other researchers, investors and banking companies